1998
DOI: 10.1046/j.1365-2222.1998.00283.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of interleukin‐8 binding and function by heparin and α2‐macroglobulin

Abstract: These results point to an anti-inflammatory role for heparin and a novel, potentially, pro-inflammatory role for alpha2-macroglobulin which together indicate the importance of cytokine-binding macromolecules in determining net cytokine function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 41 publications
4
40
0
1
Order By: Relevance
“…Subsequently, it was shown that the binding of IL-8 to HUVECs was competed with GAGs in the order of efficacy, heparin Ͼ HS Ͼ dermatan sulfate Ͼ chondroitin sulfate, indicating the relative affinity of IL-8 for heparin and HS (9). Functionally, soluble GAGs had an inhibitory effect on target cell responses, heparin and HS inhibiting IL-8-induced neutrophil calcium fluxes (9), in line with our previous observation that heparin inhibits IL-8-induced neutrophil chemotaxis (21).…”
Section: Discussionsupporting
confidence: 73%
“…Subsequently, it was shown that the binding of IL-8 to HUVECs was competed with GAGs in the order of efficacy, heparin Ͼ HS Ͼ dermatan sulfate Ͼ chondroitin sulfate, indicating the relative affinity of IL-8 for heparin and HS (9). Functionally, soluble GAGs had an inhibitory effect on target cell responses, heparin and HS inhibiting IL-8-induced neutrophil calcium fluxes (9), in line with our previous observation that heparin inhibits IL-8-induced neutrophil chemotaxis (21).…”
Section: Discussionsupporting
confidence: 73%
“…While binding does not necessarily imply an effect on function, we showed an inhibitory effect of heparin on IL-8-induced neutrophil chemotaxis in microBoyden chambers (43). These observations have since been confirmed and extended to the inhibitory effect of heparin on IL-8 bound to endothelial cell surface heparan sulfate proteoglycans (44).…”
Section: Discussionsupporting
confidence: 63%
“…Furthermore, heparin has displayed a diverse range of in vitro antiinflammatory and immunomodulatory effects, including inhibitory effects upon leukocyte recruitment [15], neutrophil chemotaxis [16], neutrophil elastase [17] and chemokines, such as IL-8 [18]. Excess neutrophil elastase activity plays a key role in contributing to airway obstruction in CF by multiple mechanisms, including stimulating IL-8 production [19] and mucus secretion [20], impairing ciliary function [21], and potentially desiccating airway secretions by activating epithelial sodium channels [22].…”
mentioning
confidence: 99%